Hubungan Antara Komunikasi Interpersonal Dengan Iklim Organisasi Pada Pegawai SMA Negeri 1 XIII Koto Kampar Kabupaten Kampar-Riau - Azrimul Azrimul; Masyhuri Masyhuri (Kutubkhanah, 2014)
This research were aimed to find out the relationship between the interpersonal communication and with the climate organization at employees SMAN I XIII Koto Kampar, Riau. The data were collected by using interpersonal communication scales and climate organization scales.The total number of the subjects were 21. Data were analyzed by using Kendal correlation analisys, by using SPSS verson 10.0 statistical program as a tool. The result of research showed there were correlation between the interpersonal communication with the climate organization significantly. The result showed R = 0.754 and adjusted R Square (R2) = 0.529) and F = 148,32. there were correlation positively between the interpersonal communication with climate organization.